Flexibility Training and Functional Ability in Older Adults: A Systematic Review - Liza Stathokostas; Robert M. D. Little; A. A. Vandervoort; Donald H. Paterson (Journal of Aging Research)
Background. As indicated in a recent systematic review relating to Canada’s Physical Activity Guidelines for Older Adults, exercise interventions in older adults can maintain or improve functional abilities. Less is known about the role of flexibility in the maintenance or improvement of functional abilities, and there currently does not exist a synthesis of the literature supporting a consensus on flexibility training prescription. Purpose. To systematically review the effects of flexibility-specific training interventions on measures of functional outcomes in healthy older adults over the age of 65 years. Methods. Five electronic databases were searched for intervention studies involving concepts related to aging, flexibility, functional outcomes, and training interventions. After evaluating the articles for relevance, 22 studies were considered. Results. The results suggested that while flexibility-specific interventions may have effects on range of motion (ROM) outcomes, there is conflicting information regarding both the relationship between flexibility interventions and functional outcomes or daily functioning. Conclusions. Due to the wide range of intervention protocols, body parts studied, and functional measurements, conclusive recommendations regarding flexibility training for older adults or the validity of flexibility training interventions as supplements to other forms of exercise, or as significant positive influences on functional ability, require further investigation.